2017
DOI: 10.1021/acs.molpharmaceut.7b00496
|View full text |Cite
|
Sign up to set email alerts
|

Application of Monodisperse PEGs in Pharmaceutics: Monodisperse Polidocanols

Abstract: Polydisperse PEGs are ubiquitously used in pharmaceutical industry and biomedical research. However, the monodispersity in PEGs may play a role in the development of safe and effective PEGylated small molecular drugs. Here, to avoid the polydispersity in polidocanol, the active ingredient in a clinically used drug, a macrocyclic sulfate-based strategy for the efficient and scalable synthesis of monodisperse polidocanols, their sulfates, and their methylated derivatives, was developed. TLC and HPLC analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Here, the use of monodisperse PEGs (i.e. pure single homologs) instead of polydisperse PEGs is rapidly gaining importance, since it improves bio-activity and safety, allowing optimal and reproducible therapeutic results [5,6]. Monodisperse PEGs are also valuable standards for many analytical methods, including size exclusion chromatography and various spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the use of monodisperse PEGs (i.e. pure single homologs) instead of polydisperse PEGs is rapidly gaining importance, since it improves bio-activity and safety, allowing optimal and reproducible therapeutic results [5,6]. Monodisperse PEGs are also valuable standards for many analytical methods, including size exclusion chromatography and various spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an oligoethylene glycol macrocyclic sulfate-based strategy for the efficient synthesis of monodisperse polyethylene glycols (M-PEGs) was developed in this group , with which a series of M-PEGylated small molecular drugs with improved solubility, quality, and drug efficacy have been developed. In contrast, the development of M-PEGylated biologics is far more challenging because M-PEGs above 4000 Da are still beyond the reach of current synthetic methods, however PEGs above 4000 Da are crucial to achieve the valuable “stealth” effects for biologics. To this end, solid phase peptide synthesis (SPPS) was employed to conveniently prepare M-OEG polyamides as amide bond-containing M-PEGs above 4000 Da, which showed high monodispersity, biocompatibility, and tunable biodegradability. , …”
Section: Introductionmentioning
confidence: 99%
“…With the development of novel synthetic methods for M-PEGs, M-PEGs and alternatives have been increasingly used biomedicine. Now, some low molecular weight M-PEGs and derivatives are commercially available. Recently, M-PEGs modified drugs, peptides, and imaging agents were developed in this group. It was found that the monodispersity of PEG is crucial for achieving optimal physicochemical and biological properties. Moreover, manipulating the size of M-PEGs has been proven as a convenient and efficient way to fine-tune the properties of M-PEG-based materials.…”
Section: Introductionmentioning
confidence: 99%